Respuestas

2013-12-23T18:27:48+01:00
7(18-x)-6(3-5x)=-(7x+9)-3(2x+5)-12

7(-x+18)-6(-5x+3)=-(7x+9)-3(2x+5)-12

7(-x+18)-6(-5x+3)=(-7x-9)+(-3(2x)-3(5))-12

7(-x+18)-6(-5x+3)=(-7x-9)+(-6x-15)-12  

7(-x+18)-6(-5x+3)=-7x-9-6x-15-12

7(-x+18)-6(-5x+3)=-13x-36  

(7(-x)+7(18))-6(-5x+3)=-13x-36

(-7x+126)-6(-5x+3)=-13x-36

(-7x+126)+(-6(-5x)-6(3))=-13x-36

(-7x+126)+(30x-18)=-13x-36

-7x+126+30x-18=-13x-36

23x+108=-13x-36

23x+108+13x=-36

36x+108=-36

36x=-108-36

36x=-144

x=-144/36

x=-4

¡La mejor respuesta!
2013-12-23T18:29:24+01:00
7(18-x)-6(3-5x) = -(7x+9)-3(2x+5)-12
primero resolvemos todos las operaciones marcadas 
126-7x -18+30x= -7x-9-6x-15-12
108+23x=-13x-36
23x+13x=-36-108
36x= -144
x= -144/36
x= -4

Espero te ayude!
Si tienes duda, pregunta!